DEVELOPMENT AND EVALUATION OF SUPPLEMENTARY LESSONS IN TEACHING SCIENCE INTEGRATING CAI MATERIALS FOR HIGH SCHOOL HEARING-IMPAIRED (Proceedings of International Conference on Special Education, 2017)
This study was undertaken to develop and evaluate Supplementary Lessons in Teaching Science Integrating Computer-Assisted Instructions design for Paaralang Pag-ibig at Pag-asa students. This is a response to the dearth of curriculum materials in science for the hearing-impaired high school students. Specifically, the study intended to identify the content of CAI materials in science for hearing-impaired. Prepare activities in science integrating CAI materials. Try-out the lessons to get information regarding its suitability, clearness of directions and adequacy of time allotment. Evaluate it according to practicality, skills learned, vocabulary, subject content and guidance needed.Designing lessons in science integrating CAI materials will positively enable the teachers to teach a certain degree of success in the conduct of activities which might be the starting point of more encouraging performance.The study focused on the development and evaluation of Supplementary Lessons in Teaching Science Integrating CAI Materials for High School Hearing-Impaired. It follows four stages of development, namely: Stage I- Planning, Stage II- Writing, Stage III- Carry-out stage, and Stage IV- Evaluation.Based on the result, the developed supplementary lessons integrating CAI material are able to meet the needs of the students. The material used in the lessons is readily available, interesting, varied and provide clear directions. It also give abundant skills that are useful in their daily living. Students with low abilities may improve their performance.The following recommendations are made wherein the supplementary lessons in teaching science integrating CAI materials be used as teaching aid for the hearing impaired. Finally, extensive research should be made to determine the effectiveness of the developed materials. All the developed materials should be tried out.